Drying kinetics and quality of tray dried peanut milk residue - Poojitha, P. (2023)
The research was aimed to prepare muffins using groundnut milk residue. Groundnut or Peanut (Arachis hypogaea) is one of the most consumed legumes in the world. Groundnut is also a prominent source of plant-based milk. The groundnut milk was prepared by the conventional method with 1:2 ratio of water. The residue was tray-dried at different temperatures (60, 70, 80°C) to study the drying kinetics. Physical and chemical properties of optimized groundnut milk residue powder were analysed. Muffins were developed using milk residue. Quality parameters and sensory analyses were also done for the product obtained from milk residue. The results indicated that groundnut milk residue dried at 70ºC had less water absorption capacity and more water solubility index. Also, the powder retained colour when dried at 70°C. The experimental data were fitted to five mathematical models. Wang and Singh's model was found to have the best fit with R² value of 0.9932. The increase in temperature promotes drying at a faster rate.